Fertilizing Potential of Separated Biogas Digestates in Annual and Perennial Biomass Production Systems - Ehmann, Andrea; Thumm, Ulrich; Lewandowski, Iris (Frontiers in Sustainable Food Systems, 2018)
Digestates produced by the increasing number of biogas plants require appropriate treatment or recycling. This study investigates the fertilizing potential of separated biogas digestates. These contain valuable nutrients and can be used in agriculture to close the nutrient cycle. Multi-year field experiments were established at two challenging sites in south-west Germany in 2010; results from six years are shown here. The objectives were to determine 1) whether separated digestates can complement or substitute mineral fertilizers and 2) their effect on long-term yield performance in different biomass cropping and fertilization systems. The fertilizing performance was assessed in a split-plot design with four replications using three cropping systems: 1) perennial grassland; 2) intercropping of triticale and clover grass; 3) silage maize. Five N fertilization treatments were applied, each at 150 kg N ha-1: mineral fertilizer (calcium ammonium nitrate) combined solid digestate fraction and mineral fertilizer solid digestate fraction combined liquid digestate fraction and mineral fertilizer liquid digestate fraction. The influences of site, cropping system, year and fertilization treatment were highly significant. The mineral fertilizer and combination ‘liquid digestate fraction + mineral fertilizer’ mostly led to the highest quantitative biomass yields in all cropping systems at both sites. Fertilization with solid digestate fraction produced lowest yields in all fertilized plots, with results very often not significantly different from the untreated control. Maize achieved relatively high yields in years with favorable weather conditions; unfavorable conditions led to low yields. The grassland and intercropping systems were less susceptible to weather conditions, producing a more constant biomass supply irrespective of site, treatment and year. The separated biogas digestates were found to have a comparable effect to mineral fertilizer on biomass yield, but this varied with cropping system. In the intercropping system, complete substitution was possible. The solid fraction is more likely to contribute positively to soil humus in annual systems. In general, the combined application of digestate and mineral fertilizer is highly recommendable to meet crops’ short- and long-term N demand, even on challenging sites. In this study, it allowed a mineral fertilizer input reduction of 66%.